2017
DOI: 10.2147/jpr.s135382
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of middle cluneal nerve entrapment

Abstract: ObjectEntrapment of the middle cluneal nerve (MCN) under the long posterior sacroiliac ligament (LPSL) is a possible, and underdiagnosed, cause of low-back and/or leg symptoms. To date, detailed anatomical studies of MCN entrapment are few. The purpose of this study was to ascertain, using cadavers, the relationship between the MCN and LPSL and to investigate MCN entrapment.MethodsA total of 30 hemipelves from 20 cadaveric donors (15 female, 5 male) designated for education or research, were studied by gross a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 29 publications
0
26
0
4
Order By: Relevance
“…The MCN originates at S1–S4 ( Fig. 1 ) [ 12 ]. It passes below and sandwiches the long posterior sacroiliac ligament (LPSL) between the posterior superior iliac spine (PSIS) and the posterior inferior iliac spine (PIIS) and courses over the iliac crest to the buttocks [ 9 , 12 , 13 ].…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…The MCN originates at S1–S4 ( Fig. 1 ) [ 12 ]. It passes below and sandwiches the long posterior sacroiliac ligament (LPSL) between the posterior superior iliac spine (PSIS) and the posterior inferior iliac spine (PIIS) and courses over the iliac crest to the buttocks [ 9 , 12 , 13 ].…”
Section: Anatomymentioning
confidence: 99%
“…It passes below and sandwiches the long posterior sacroiliac ligament (LPSL) between the posterior superior iliac spine (PSIS) and the posterior inferior iliac spine (PIIS) and courses over the iliac crest to the buttocks [ 9 , 12 , 13 ]. Although Tubbs et al [ 9 ] claimed that the MCN cannot be entrapped because it runs superficial to the LPSL, others considered MCN-E possible because the lateral branches of the dorsal sacral rami penetrate the LPSL [ 12 , 13 ]. In patients with LBP the putative cause was MCN-E [ 14 - 16 ].…”
Section: Anatomymentioning
confidence: 99%
“…14 It passes through the LPSL between the PSIS and the PIIS, slants over the iliac crest, and runs to the buttocks. 14,18,25 According to Tubbs et al, 25 the nerve cannot be entrapped because it runs superficial to the LPSL. McGrath and Zhang 18 reported that because the MCN penetrates the LPSL, its entrapment can elicit pain.…”
Section: Lbp Due To Mcn-ementioning
confidence: 99%
“…McGrath and Zhang 18 reported that because the MCN penetrates the LPSL, its entrapment can elicit pain. In a cadaveric study, Konno et al 14 reported that 30% of the MCNs on 30 sides featured a branch that traversed under the LPSL. Their anatomical findings suggested that MCN-E is not a rare clinical entity.…”
Section: Lbp Due To Mcn-ementioning
confidence: 99%
See 1 more Smart Citation